A Study on the Epidemiology and Aetiology of Acute Gastroenteritis in Adult Patients Presenting at the Infectious Diseases Hospital in Tirana, Albania - Stroni, Gentian P. (Balkan Med J, 2014)
BACKGROUND: Acute gastroenteritis remains a common cause of hospital emergency room visits in Albania. However, the aetiology of severe gastroenteritis leading to hospitalization in adults frequently remains unclear. AIMS: Our objective was to study the epidemiology and causes of community-acquired, acute gastroenteritis in adult patients presenting to hospital. STUDY DESIGN: Cross sectional study. METHODS: A prospective study was conducted from January 2010 to January 2012, among patients ≥15 years old with community-acquired gastroenteritis presenting to the emergency room of the University Hospital “Mother Theresa” in Tirana, Albania. Stool samples and rectal swabs were collected from the patients for microbiological testing. RESULTS: The median age of the study patients was 33 (15–88) years and 577 (58%) were females. The median age of males was 35 (15–87) years. The vast majority of cases occurred in urban area (849, 85%), p<0.01. Patients were admitted throughout the year with peak admissions for patients infected by bacterial pathogens in summer and those affected by viral pathogens in autumn. A total of 917 (91.7%) patients underwent a laboratory examination. The overall isolation rate was 51%. Bacterial pathogens were found in 29%, viral pathogens in 19% and protozoal pathogens in 2.5% of patients. No aetiological agent or other cause of acute diarrhoea was found in 449 (49%) patients. Twenty-nine (3.2%) patients were hospitalized. CONCLUSION: Despite extensive laboratory investigations, enteropathogens were detected in only 51% of adult patients who presented to the hospital ER with acute gastroenteritis. Viral infections ranked as the second most common cause of gastroenteritis in adults.